DESIGN AND DEVELOPMENT OF A SMALL-SCALE 5-DOF 3D PRINTED ROBOT - Trubayev, Sanjar (Nazarbayev University School of Engineering and Digital Sciences, 2022)
The combination of industrial robots and additive manufacturing technologies provides manufacturers with the ability to fabricate large and heavy products with high dimensional accuracy and automate this manufacturing process. The robotics industry, however, lacks its own manufacturing facilities and has to outsource special orders to manufacturing companies which imply additional expenses and time delays. Therefore, the relevance of integrating additive manufacturing into the robotics industry is the object of research since it can considerably favor the development of this industry. The primary aim of this work is to develop and design 5 DOF 3D printed robot manipulator. The developed model of the manipulator was tested via numerical simulations. Based on the simulation results, the model was then topologically optimized. The optimized model was manufactured using the method of fused deposition modelling. The manipulator was actuated by the six servomotors controlled by the rotary potentiometers and tested by performing pick-and-place operations. The motion accuracy of the robot was affected by such factors as a backlash and motor vibrations due to an inappropriate power supply. The total material and equipment cost can be reduced by additional optimization and obtaining the balance between the infill density of components and their mechanical strength. According to the results of the conducted research, fused deposition modeling is the feasible solution for manufacturing prototypes of robot manipulators and real models for educational purposes. Such integration of 3D printing into the manufacturing facilities of the robotics industry favors the development of this industry since in-situ production and prototyping of fully 3D-printable robots requires less expenses with shorter production time. Keywords: robot manipulator, additive manufacturing, robotics
Keywords: robot manipulator; additive manufacturing; robotics; type of access: gated access; Research Subject Categories::TECHNOLOGY